Relation of E1 pygmy and toroidal resonances - Nesterenko, V. O.; Repko, A.; Reinhard, Paul-Gerhard; Kvasil, J. (EPJ Web of Conferences, 2015)
A possible relation of low-lying E1 strength ("pygmy resonance") and toroidal strength is analyzed by using Skyrme random-phase-approximation (RPA) results for the strength functions, transition densities and current fields in 208Pb. It is shown that the irrotational pygmy motion can appear as a local manifestation of the collective vortical toroidal dipole resonance (TDR) at the nuclear surface. The RPA results are compared to unperturbed (1ph) ones. Owned by the authors, published by EDP Sciences, 2015.
CRIS-Team Scopus Importer:2023-07-24